Pengaruh Profitabilitas, Leverage, Opini Auditor, Firm Size, Umur Perusahaan Terhadap Audit Delay Pada Perusahaan LQ-45 Yang Terdaftar Di BEI Periode 2016-2018 - Eko Siswanto; Fatchurrochman Fatchurrochman (Universitas Merdeka Madiun, 2021)
Abstract— The purpose of this study is to seek the profitability, leverage, auditor's opinion, firm size, company age on audit delay. Purposive sampling technique was used in sampling. The annual reports of LQ-45 Index enterprises registered on the IDX during 2016 to 2018 are used as secondary data sources. Data analysis was performed by multiple linear regression. Hypothesis testing results show that the profitability variable does not affect audit postponement, leverage variable has a positive effect on audit delay, auditor opinion variable influences audit delay, firm size variable does not affect audit deferment, while age of corporation variable has’t not react on audit delay. Keywords—: Profitability; Leverage; Auditor Opinion; Firm Size; Company Age .